A cost-effective breast cancer screening strategy for Urban China: Findings from a Shenzhen-based modeling study - Changqing Tu; Yuke Zhong; Huan Li; Haifeng Qi; Qian Lu; Xuesen He (PLoS ONE, 2026)
Background Early detection through breast cancer screening significantly enhances survival rates and reduces mortality. However, financial constraints in low- and middle-income countries often limit the implementation of large-scale screening programs. This study evaluates the cost-effectiveness of a combined Clinical Breast Examination (CBE), Breast Ultrasound (BUS), and supplementary Mammography (MAM), screening strategy for women aged 35–65 in Shenzhen, China. It further identifies optimal screening protocols by analyzing variations in screening frequency, starting/ending ages, and long-term health outcomes. Methods A Markov model was developed from a societal perspective to assess the lifetime cost-effectiveness of biennial (CBE + BUS)+MAM screening for women aged 35–65. A total of 27 strategies were simulated, varying screening frequency (annual, biennial, triennial), age at initiation (35, 40, 45), age at cessation (65, 69, 70), and modality combinations. Quality-Adjusted Life Years (QALYs) served as the primary health outcome metric. Incremental Cost-Utility Ratios (ICURs) were calculated, with one-way and second-order Monte Carlo sensitivity analyses conducted to evaluate parameter uncertainty. Results Among 699,600 participants, 724 breast cancer cases were detected (detection rate: 103.49 per 100,000), with 88% diagnosed at early stages. The current Shenzhen strategy – biennial Clinical Breast Examination combined with Breast Ultrasound and supplementary Mammography ((CBE + BUS)+MAM/2year/35_65) – demonstrated an ICUR of 140,915 CNY/QALY compared to no screening, below one times the per capita GDP (indicating cost-effectiveness). In various scenarios, while the (CBE + BUS)+MAM/3year/45_65 strategy had a lower ICUR (95,545 CNY/QALY), the ICUR for the current strategy versus this alternative was 518,121 CNY/QALY, still below the willingness-to-pay threshold of 537,000 CNY (three times GDP). Second-order Monte Carlo simulations confirmed the robustness of the current strategy in 76% of scenarios. Conclusion The (CBE + BUS) +MAM/2year/35_65 strategy was identified as the optimal choice among 27 alternatives, providing a cost-effective balance between early detection and resource efficiency. This evidence solidifies its use and offers a strategic framework for allocating public health resources in Shenzhen and comparable urban settings.